SUPPLEMENTATION OF CHITOSAN AS THE SHRIMP SHELL DERIVATIVES IN RATIONS ON GROWTH AND BLOOD TOTAL CHOLESTEROL LEVELS IN LOCAL DUCK - pretti sitompul (Universitas Sumatera Utara, 2016)
ABSTRACT High levels of total cholesterol be a limiting factor that causes freely against the consumption of meat and duck eggs by peoples. For it was conducted a study in May-September 2015 to observe the supplementation effect of chitosan from shrimp shell in the diet on growth and total cholesterol levels in the blood of ducks using a completely randomized design with 4 treatments and 5 replications. The treatments consisted of T0 = basal diet +0% chitosan; T1 = basal diet + 9,05% powders of shrimp shell; T2 = basal diet + 1,5% chitosan derivatives of shrimp shell; T3 = basal diet + 1,5% chitosan by BIOTECH SURINDO. The variables were consist of feed intake, body weight gain, feed conversion ratio and total blood cholesterol levels. The results showed that supplementation of shrimp shell’s powder, chitosan from shrimp shell and commercial chitosan in the diet decreased the total of blood cholesterol levels and growth performances in local ducks (P<0.05). The total blood cholesterol (mg/dL) on T1; T2; T3; T4 were 252,4; 224; 153; 183. While average weekly body gain also decreased 6,55%; 22,18%; dan 14,02% than control. It is concluded that suplementation of 1,5% chitosan from shrimp shell show the best result according to the total blood cholesterol and growth performances of duck. Keywords: Chitosan, shrimp shell, the total blood cholesterol of local duck.